Impaired Ventilatory and Thermoregulatory Responses to Hypoxic Stress in Newborn Phox2b Heterozygous Knock-Out Mice - Ramanantsoa, Nelina; Matrot, Boris; Vardon, Guy; Lajard, Anne-Marie; Voituron, Nicolas; Dauger, Stéphane; Denjean, André; Hilaire, Gérard; Gallego, Jorge (Frontiers in Physiology, 2011)
The Phox2b gene is necessary for the development of the autonomic nervous system, and especially, of respiratory neuronal circuits. In the present study, we examined the role of Phox2b in ventilatory and thermoregulatory responses to hypoxic stress, which are closely related in the postnatal period. Hypoxic stress was generated by strong thermal stimulus, combined or not with reduced inspired O2. To this end, we exposed 6-day-old Phox2b+/- pups and their wild-type littermates (Phox2b+/+) to hypoxia (10% O2) or hypercapnia (8% CO2) under thermoneutral (33°C) or cold (26°C) conditions. We found that Phox2b+/- pups showed less normoxic ventilation (VE) in the cold than Phox2b+/+ pups. Phox2b+/- pups also showed lower oxygen consumption (VO2) in the cold, reflecting reduced thermogenesis and a lower body temperature. Furthermore, while the cold depressed ventilatory responses to hypoxia and hypercapnia in both genotype groups, this effect was less pronounced in Phox2b+/- pups. Finally, because serotonin (5-HT) neurons are pivotal to respiratory and thermoregulatory circuits and depend on Phox2b for their differentiation, we studied 5-HT metabolism using high-pressure liquid chromatography, and found that it was altered in Phox2b+/- pups. We conclude that Phox2b haploinsufficiency alters the ability of newborns to cope with metabolic challenges, possibly due to 5-HT signaling impairments.